Examining geographic mosaics of interactions in an orchid-pollinator-fungi system of the tropical andes (2022)
The interactions between organisms are crucial for their survival and reproduction and have shaped life on earth. This proposition is developed in the Geographic Mosaic of Coevolution Theory proposed by John Thompson in 2005. In general terms, Thompson suggests that interactions lead to evolutionary processes through coevolution between interacting species. As in nature species are usually collections of populations distributed in different environments, then the interactions that occur in each population are subject to change because they are found in different environmental contexts in each locality, which can promote the adaptation of some species to others. Therefore, the key to understanding the dynamics of coevolutionary processes lies in spatial variability. The resulting process is a geographic mosaic of local adaptations of interspecific interactions, and because the mosaic is constantly changing as species co-evolve, populations diverge, and can sometimes undergo speciation. In terms of biotic interactions, Orchidaceae is a model family to approach questions of evolutionary ecology, considering its specialized and obligate mutualistic relationships with both its pollinators and mycorrhizal fungi. Considering the framework exposed by Thompson, the central question of this research is whether populations of the Dichaea andina orchid located in different regions of the Colombian Andes differ locally in their mutualistic partners (fungi and pollinators) and have formed geographic mosaics in their interactions. This document is divided into four chapters. The first chapter focused on the detailed description of the study species, the result of which was the proposal of a new species of orchid. The second chapter addressed questions about the natural history of the D. andina orchid. Here it was determined if there were variations among populations in terms of the phenology of the species, floral traits, mating system, and pollination. We found that, for all populations, the phenology followed a bimodal pattern with two flowering peaks per year in May and October. Dichaea andina is a completely allogamous and self-incompatible species, it produces floral fragrances mainly composed of 2-(4-Methoxyphenyl) ethanol and 2-Methoxyphenol, and was exclusively pollinated by Euglossa nigropilosa bee. That is, for the orchid-pollinator interaction we did not detect a geographic mosaic. The third chapter explored the orchid-fungi interaction and assessed differences in fungal partners among populations. We found that, in each population, the plants were related to a particular set of endophytic fungi, evidencing a geographic mosaic for this type of interaction. As a mycorrhizal fungus, D. andina was associated with a Ceratobasidium fungus, which was the only one to promote seed germination in in vitro experiments. Finally, the fourth chapter quantified the genetic differences between D. andina populations, using single nucleotide polymorphisms (SNPs) as genetic markers, and evaluated the overlap between genetic and geographic distances. We found that there was little genetic differentiation between orchid populations and that geography does not seem to be explaining the minimal genetic distances detected. Under this scenario, we propose that considerable gene flow has been maintained to prevent differentiation, probably explained by the great potential for long-distance dispersal of the tiny seeds.